Reduction of Pain Sensitivity After Somatosensory Therapy in Adults with Cerebral Palsy - Riquelme, Inmaculada; Zamorano, Anna; Montoya, Pedro (Frontiers in Human Neuroscience, 2013)
Objective. Pain and deficits in somatosensory processing seem to play a relevant role in cerebral palsy (CP). Rehabilitation techniques based on neuroplasticity mechanisms may induce powerful changes in the organization of the primary somatosensory cortex and have been proved to reduce levels of pain and discomfort in neurological pathologies. However, little is known about the efficacy of such interventions for pain sensitivity in CP individuals. Methods. Adults with cerebral palsy participated in the study and were randomly assigned to the intervention (n=17) or the control group (n=20). The intervention group received a somatosensory therapy including 4 types of exercises (touch, proprioception, vibration, and stereognosis). All participants were asked to continue their standardized motor therapy during the study period. Several somatosensory (pain and touch thresholds, stereognosis, propioception, texture recognition) and motor parameters (fine motor skills) were assessed before, immediately after and three months after the therapy (follow-up). Results. Participants of the intervention group showed a significant reduction on pain sensitivity after treatment and at follow-up after three months, whereas participants in the control group displayed increasing pain sensitivity over time. No improvements were found on touch sensitivity, proprioception, texture recognition or fine motor skills. Conclusions. Data suggest the possibility that somatosensory therapy was effective in eliciting changes in central somatosensory processing. This hypothesis may have implications for future neuromodulatory treatment of pain complaints in children and adults with cerebral palsy.